SLX4 interacts with RTEL1 to prevent transcription-mediated DNA replication perturbations - Takedachi, A; Despras, E; Scaglione, S; Guérois, R; Guervilly, J H; Blin, M; Audebert, S; Camoin, L; Hasanova, Z; Schertzer, M; Guille, A; Churikov, D; et al. (Nature structural & molecular biology, 2020)
The SLX4 tumor suppressor is a scaffold that plays a pivotal role in several aspects of genome protection, including homologous recombination, interstrand DNA crosslink repair and the maintenance of common fragile sites and telomeres. Here, we unravel an unexpected direct interaction between SLX4 and the DNA helicase RTEL1, which, until now, were viewed as having independent and antagonistic functions. We identify cancer and Hoyeraal-Hreidarsson syndrome-associated mutations in SLX4 and RTEL1, respectively, that abolish SLX4-RTEL1 complex formation. We show that both proteins are recruited to nascent DNA, tightly co-localize with active RNA pol II, and that SLX4, in complex with RTEL1, promotes FANCD2/RNA pol II co-localization. Importantly, disrupting the SLX4-RTEL1 interaction leads to DNA replication defects in unstressed cells, which are rescued by inhibiting transcription. Our data demonstrate that SLX4 and RTEL1 interact to prevent replication-transcription conflicts and provide evidence that this is independent of the nuclease scaffold function of SLX4.
Keywords: genetická transkripce; protein FANCD2; dyskeratosis congenita; Recombinases; DNA Helicases; Fetal Growth Retardation; Humans; HeLa buňky; Microcephaly; mikrocefalie; Transcription, Genetic; zárodečné mutace; rekombinasy; lidé; DNA-helikasy; mentální retardace; DNA Replication; Intellectual Disability; Germ-Line Mutation; HeLa Cells; replikace DNA; růstová retardace plodu; Dyskeratosis Congenita; Fanconi Anemia Complementation Group D2 Protein